Muhammadiyah: The Challenge of Rising Conservatism - Nubowo, Andar (2018)
Ostensibly a champion of moderate Islam in Indonesia, Muhammadiyah is itself challenged by a growing conservatism in Indonesian politics. How should Indonesia’s second largest Muslim organisation cope with this turn towards conservatism?